Jigsaw as a community learning strategy: Improving students' social attitudes in digestive system material - Vina Septiani; P. Paidi; S. Syamsurizal; Rahmawati Darussyamsu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Social attitudes are needed by students in improving communication and collaboration skills in the 4.0 industrial revolution era. This study aimed to identify the effect of the jigsaw learning model as a community learning strategy on students' social attitudes in digestive system material. This quasi-experimental research was using a non-equivalent pretest-posttest control group design. The population used was eighth-graders in Padang. The samples involved were two groups selected through a simple random sampling technique. The instrument used was observation sheets to measure four aspects of social attitudes, including social discipline, tolerance, self-confidence, and collaboration. Data were analyzed using one-way ANCOVA. The result showed that the jigsaw as a community learning strategy has a significant effect on students' social attitudes (p-value < 0.05). As a recommendation, the jigsaw learning model can be applied to promote students' social attitudes.